PNEUMOCOCCAL INFECTION AND ASSOCIATED DISEASES - A SERIOUS PROBLEM OF MODERN HEALTH CARE - A.A. Baranov; L.S. Namazova; V.K. Tatochenko (Union of pediatricians of Russia, 2008)
Pneumococcal infection is one of the most widespread reasons for the development of infections of the respiratory passages (otitis, sinusitis) in children. At the same time, it may act as an etiological factor of severe urgent conditions, such as pneumococcal meningitis and pneumococcal pneumonia, especially in children under 2 years old. A reliable method for preventing this infection is specific immunological prophylaxis. The article covers in detail the issue of vaccination in Russia and in other countries. The necessity of vaccination of all infants is demonstrated, as well as the necessity of participation in resolving this issue not only of pediatricians but governmental institutions as well in order to enhance safety and efficiency of vaccination and include this vaccine into the national calendar.Key words: pneumococcal infection, forms, complications, vaccination, national vaccination calendar, risk groups, children.